PENGARUH STEREOTYPE GENDER TERHADAP KONSEP DIRI PEREMPUAN - Ismiati Ismiati (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2018)
Stereotypes about women's lower self-concept than men not only found in everyday speaking, but is also supported by the results of research and scientific studies. Some stereotypes that have rooted and considered as absolutely truth in the society like women not independent, timid, indecisive, not suitable to be a leader, and irrational. These kinds of stereotypes cause some impacts on women perceptions themselves. Actually this is a form of self-concept that inadvertently learned and eventually internalized in women. In other words, a stereotype has been shackled feelings, thoughts and perspectives of women against themselves which affects the low self-esteem.